2012
DOI: 10.1258/acb.2012.012084
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prandial status on the comparison of capillary glucose meter and venous plasma glucose measurements in healthy volunteers

Abstract: In healthy volunteers, both glucose meters showed a systematic positive bias one hour after breakfast. The significance of this finding in diabetes remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Another consideration is the difference in sample type. In the fasting state, capillary whole blood glucose is 11% lower when compared with venous plasma glucose [33]. This difference is mostly due to the difference in water content between the two samples.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another consideration is the difference in sample type. In the fasting state, capillary whole blood glucose is 11% lower when compared with venous plasma glucose [33]. This difference is mostly due to the difference in water content between the two samples.…”
Section: Discussionmentioning
confidence: 93%
“…POCT proved to be most valuable for the diagnosis of Type 2 diabetes utilizing fasting values. In addition, there is an arterio-venous glucose gradient that becomes more pronounced following a carbohydrate load due to improved peripheral glucose uptake [33]. 2a).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue uptake of glucose produces an arterial-capillaryvenous gradient in glucose concentration, first described around 160 years ago [1]. Multiple publications have confirmed that, after ingestion of an oral nutrient load, a glucose gradient occurs of~1-2 mmol/l in magnitude [2][3][4][5][6][7][8][9][10][11][12][13]. In healthy volunteers, the gradient in peripheral tissue is minimal in the fasting state and maximal at~30-60 min after oral carbohydrate intake [2].…”
Section: Introductionmentioning
confidence: 99%
“…Additional methodology is described in detail elsewhere. 2 Statistical comparisons were undertaken using unpaired two tailed t-tests, simple linear regression and 2 tests. P < 0.05 was considered to be significant.…”
Section: Methodsmentioning
confidence: 99%
“…This study aims to add to our knowledge of the random glucose range by describing the one hour post breakfast venous plasma glucose results from healthy individuals, obtained as part of a previous study. 2 …”
Section: Introductionmentioning
confidence: 99%